Disney : Scary Storybook Collection - Various; Disney Storybook Artists; Disney Book Group (New York : Disney Press, 2008)
Gently spooky collection of easy-to-read stories based on Disney and Pixar cartoons.
Keywords: Horror tales, American; Disney characters; Juvenile fiction; Childrens stories, American; Short stories, American; Children Short stories